Reinventing Tradition: Russian-Jewish Literature between Soviet Underground and Post-Soviet Deconstruction - Smola, Klavdia (Jews of Russia & Eastern Europe and Their Legacy, 2023)
How was the Jewish tradition reinvented in Russian-Jewish literature after a long period of assimilation, the Holocaust, and decades of Communism? The process of reinventing the tradition began in the counter-culture of Jewish dissidents, in the midst of the late-Soviet underground of the 1960-1970s, and it continues to the present day. In this period, Jewish literature addresses the reader of the ‘post-human’ epoch, when the knowledge about traditional Jewry and Judaism is received not from the family members or the collective environment, but rather from books, paintings, museums and popular culture. Klavdia Smola explores how contemporary Russian-Jewish literature turns to the traditions of Jewish writing, from biblical Judaism to early-Soviet (anti-)Zionist novels, and how it ‘re-writes’ Haskalah satire, Hassidic Midrash or Yiddish travelogues.